Digtets formater: Ny dansk lyrik mellem tekst, værk og koncept - Schmidt, Michael Kallesøe; Rasmussen, Krista Stinne Greve; Skriver, Svend (Danske Studier, 2024)
The article examines how key terminology of textual criticism can be taken as a starting point for the investigation of material aspects of contemporary poetry. The concepts in question are ‘text’ and ‘work’ as defined by Johnny Kondrup (2013). The authors take the view that the categorical definition of text and work can be supplemented by a hermeneutical dimension, thus taking various versions of works and the influence of their respective media (blog, book etc.) on the percipient into account. In connection with the theoretical considerations, a handful of recent works by Lea Marie Løppenthin, Olga Ravn, Mikkel Thykier, Caspar Eric, and Simon Grotrian are discussed. By using the format as a point of departure rather than applying a more conventional practice of close reading, the authors argues for a broad-spectred approach to literary analysis which focuses on aspects of the conception and reception of contemporary poetry.